Analisis Laporan Arus Kas Untuk Menilai Kinerja Keuangan Pada Hybe Corporation - Widad Yuliawati Mokhtar; Dista Anggini; Ratih Kusumastuti (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
One of the company's asset accounts, cash plays an important role in financing the company's operations. The actual cash position in the company's operational activities is disclosed in the statement of cash flows. Cash flow ratios can be used to assess how an organization's financial performance has changed from year to year. The purpose of this research is to ascertain how the financial performance of HYBE CORPORATION can be evaluated using a cash flow statement using a quantitative descriptive approach. The study findings show that HYBE CORPORATION's financial performance is not stable. If we look at it globally, the cause of this is due to Covid-19 from 2020–2021, and research data also shows an increase in 2022, as seen from HYBE CORPORATION's financial performance based on research on cash flow reports using the cash flow ratio during the analysis period.